The disclosure of corporate social responsibility which is presented in the financial information on the internet - Petraškaitė, Vytautė; Rudžionienė, Kristina (Buhalterinės apskaitos teorija ir praktika, 2014)
Development of Corporate social responsibility (CSR) companies tend to disclose CSR information in annual, environmental protection, social responsibility reports and website. In Lithuania presentation of CSR is not necessary, but every year more companies disclose social information. One of CSR disclosure ways is the Internet. Purpose of this article - to investigate the level of CSR disclosure which is presented in the financial information on the Internet. Results show that firms in High-Profile environmentally sensitive industries tend to disclose more CSR information than those in Low-Profile environmentally sensitive industries. The results also indicated that the content, level disclosed on the internet are quite different. Only the little number of companies disclose their information of CSR on the internet.